(untitled) (REMUNOM, 2024)
Alzheimer’s Disease (AD) is a disease responsible for affecting millions of people globally characterized by the accumulation of Beta-Amyloid and TAU protein plaques in the brain, in this context, recent studies have addressed compounds present in green tea (Camellia sinensis), such as Epicatechin Gallate (EGC) and Epigallocatechin Gallate (EGCG), for their therapeutic potential in the prevention of AD and other neurodegenerative disorders, although its therapeutic efficacy depends on crossing the blood-brain barrier (BBB) in the brain. Therefore, the objective of the study proposed, through in silico tools, the molecular modification of Epicatechin and Epigallocatechin Galates by increasing the permeability of these compounds while preserving the affinity with Alzheimer’s-related targets. A total of 221 analogues were performed, however, according to the determined inclusion criteria, only 6 molecules were used, which showed relevant affinity with the targets of interest, as well as with targets beyond DA such as PGD, TERT and BCL2 targets, according to the SwissTarget Prediction platform. Through the PreADMET platform, it was possible to observe the ability to cross the BBB and intestinal absorption (HIA) moderately and high plasma protein binding. In addition, the compounds did not demonstrate mutagenic potential in the Ames test, good safety margins regarding LD50, hepatotoxicity and neurotoxicity by ProTox III. Among the analogues produced and analyzed, EGC. S1, EGC. S2 and EGCG. S1 stood out as the most promising, presenting the highest permeability and absorption values, as well as an affinity of more than 60% with the BACE1 and MAPT targets related to the prevention of Alzheimer’s Disease. The other compounds showed moderate lipid solubility, permeability and absorption, with affinity for all the proposed molecular targets, in addition to being non-mutagenic and non-carcinogenic in mice, although they showed potential cardiac risks, which requires further tests for a more objective and effective development.